Model Of Partnership Agreement Between Medium Small Businesses (Smes) And Big Businesses In Realizing Joint Welfare - Rai Mantili (Fakultas Hukum, Universitas Warmadewa, 2020)
The objectives of this study is to examine the partnership agreement model between SMEs and Large Enterprises in creating shared prosperity and to examine the principles’ application of the agreement in partnership that can provide protection for SMEs in Indonesia. The research method used in this study is analytical descriptive which aims to obtain a comprehensive picture of the partnership agreement in Indonesia. Data about the business partnership agreement and its implementation are then analyzed to answer the research problem. Based on analysis, the results of this study showed that 1) the partnership agreement model between SMEs and Large Enterprises in creating shared prosperity must begin with efforts to apply the principles of the agreement and business ethics in the partnership agreement. 2) the application of the principles of agreement in partnership in practice has not yet run optimally, there are still many partnership agreements that have been deviated from the contents of the agreement. In this case the role of government is needed to provide protection to the SME group and also the Large Business group to realize social responsibility for the progress of the UKM business group.